Adaptation of a Couple-Based HIV/STI Prevention Intervention for Latino Men Who Have Sex With Men in New York City. (March 2017) - Martinez, Omar; Wu, Elwin; Frasca, Timothy; Shultz, Andrew Zach; Fernandez, M. Isabel; López Rios, Javier; Ovejero, Hugo; Moya, Eva; Chavez Baray, Silvia; Capote, Jonathan; Manusov, Justin; Anyamele, Chukwuemeka O.; et al.
Predominantly Spanish-speaking Latino men who have sex with men (MSM) and their same-sex partners continue to be at high risk for HIV and STIs. Behavioral research has identified how relationship dynamics for male couples are associated with sexual risk behavior. Connect 'n Unite (CNU), an evidence-based HIV/STI prevention intervention originally created for Black MSM and their same-sex partners, was adapted for predominantly Spanish-speaking Latino MSM and their same-sex partners on the assumption that its key elements would be translatable while its efficacy would be retained. A systematic adaptation process utilizing qualitative methods was used, including intervention adaptation sessions with 20 predominantly Spanish-speaking Latino gay couples and 10 health service providers. The process included five steps: (1) engaging community stakeholders, (2) capturing the lived experiences of Latino gay couples, (3) identifying intervention priorities, (4) integrating the original intervention's social cognitive theory into a relationship-oriented, ecological framework for Latino gay couples, and (5) adapting intervention activities and materials. The adapted intervention, which we called Latinos en Pareja or Latinos in a Relationship, incorporates elements that effective HIV prevention interventions share, including: a solid theoretical foundation; emphasis on increasing risk reduction norms, sexual communication skills and social support for protection; and guidance on how to utilize available, culturally and linguistically appropriate services. The systematic adaptation approach used for a couples-based HIV prevention intervention also can be employed by other researchers and community stakeholders to adapt evidence-based interventions that promote wellness, linkage to care, and disease prevention for populations not originally targeted.